Neuromuscular training improves knee kinematics, in particular in valgus aligned adolescent team handball players of both sexes - Barendrecht, M.; Lezeman, H. C. A.; Duysens, J.; Smiths-Engelsman, B. C. M. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to investigate the effects of added neuromuscular training (NMT), as compared to just regular training (RT), on lower extremity kinematics and single leg stability in adolescent team handball players of both sexes and to investigate whether these effects are more evident in valgus aligned athletes. Eighty adolescent team handball players (NMT: n = 49, RT: n = 31) were tested on knee kinematics in a drop jump and single leg stability in a 1-leg hop test. Based on the initial results in the drop jump test, both groups were subdivided into an above-average valgus aligned (AAVA; NMT: n = 27, RT: n = 22) and a below average valgus aligned (NMT: n = 22, RT: n = 9) group. All groups received 10 weeks of handball training either without (RT) or with in-season NMT. A significant interaction of training and valgus group was found for all absolute and for 2 out of 4 normalized knee distances in the drop jump test (p < 0.024) and for contact time after the first landing (p = 0.029). The AAVA-NMT group showed the largest relative progression (18-37%) for all these parameters. In the 1-leg hop test, a significant effect of NMT compared to RT was found for both legs (p < 0.042). Compared to RT alone, added in-season NMT has the greatest benefits on knee kinematics and single leg stability, in particular in AAVA adolescent team handball players of both sexes. The results of this study suggest that adolescent team handball players of both sexes should be given NMT, 20 minutes twice a week for 10 weeks to improve landing kinematics and single leg stability. "At risk" players with higher initial valgus angles will benefit most from this NMT.